Impact of virtual microscopy with conventional microscopy on student learning in dental histology - Alka Harish Hande; Vidya K Lohe; Minal S Chaudhary; Madhuri N Gawande; Swati K Patil; Prajakta R Zade (Wolters Kluwer Medknow Publications, 2017)
Background: In dental histology, the assimilation of histological features of different dental hard and soft tissues is done by conventional microscopy. This traditional method of learning prevents the students from screening the entire slide and change of magnification. To address these drawbacks, modification in conventional microscopy has evolved and become motivation for changing the learning tool. Virtual microscopy is the technique in which there is complete digitization of the microscopic glass slide, which can be analyzed on a computer. This research is designed to evaluate the effectiveness of virtual microscopy with conventional microscopy on student learning in dental histology. Materials and Methods: A cohort of 105 students were included and randomized into three groups: A, B, and C. Group A students studied the microscopic features of oral histologic lesions by conventional microscopy, Group B by virtual microscopy, and Group C by both conventional and virtual microscopy. The students' understanding of the subject was evaluated by a prepared questionnaire. Results: The effectiveness of the study designs on knowledge gains and satisfaction levels was assessed by statistical assessment of differences in mean test scores. The difference in score between Groups A, B, and C at pre- and post-test was highly significant. This enhanced understanding of the subject may be due to benefits of using virtual microscopy in teaching histology. Conclusion: The augmentation of conventional microscopy with virtual microscopy shows enhancement of the understanding of the subject as compared to the use of conventional microscopy and virtual microscopy alone.